Uji Perbandingan Antibiotik Profilaksis Ceftriaxone versus Cefazolin pada Bedah Obstetri dan Ginekologi - Asri Rahayu; Fita Rahmawati; Tri Murti Andayani; Ammar Siradjuddin (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Surgical site infection (SSI) is the most common complication in postoperative surgical patients which is associated with high morbidity, mortality, and cost burden. These complications can be prevented by giving proper prophylactic antibiotics. Cefazolin is a recommended prophylactic antibiotic, but in the practice in Indonesia hospital, there are still many uses of ceftriaxone. This study aimed to compare the clinical outcome and safety of cefazolin and ceftriaxone as prophylactic antibiotics in preventing SSI in obstetric and gynecological surgical patients. The study design was double-blind randomized controlled trial. The data collection was conducted from January to June 2020 at dr. Dradjat Prawiranegara Regional Hospital Serang. A total of 82 subjects who met the inclusion criteria were divided into two groups by block randomization, 41 subjects were given cefazolin and 41 subjects were given ceftriaxone. The clinical outcome was measured by preventing SSI for the effectiveness and side effects for safety outcomes in both groups. The comparison of effectiveness and side effects were analyzed using the bivariate test (chi-square or fisher’s exact test) and relative risk (RR). The study showed that the effectiveness of cefazolin was the same as ceftriaxone in preventing SSI for 30 days (RR= 0.89; p= 0.724; 95%CI: 0,193-3,133) with the number of SSI 12.2% vs 9.8%. Side effects included nausea, vomiting, and phlebitis was observed in the administration of antibiotic by intravenous push (IVP) pre-operating.  Cefazolin have safetier than ceftriaxone with the incidence of side effects were 9.8% vs 29.3% ((RR = 0,33; p= 0.003; 95% CI: 0.076-0.895).  Cefazolin is an antibiotic recommended by Indonesian Ministry of Health and the Association of Obstetrics and Gynecology.  This study encourages the use of cefazolin to prevent resistance due to ceftriaxone to overuse.